2011
DOI: 10.1002/jor.22051
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder muscle activation and coordination in patients with a massive rotator cuff tear: An electromyographic study

Abstract: Adaptive muscle activation strategies following a massive rotator cuff tear (MRCT) are inadequately understood, and the relationship among muscles during everyday activities has not been considered. Thirteen healthy subjects comprised the control group, and 11 subjects with a MRCT the patient group. Upper limb function was assessed using the Functional Impairment test-hand, neck, shoulder, and arm (FIT-HaNSA). Electromyography (EMG) was recorded from 13 shoulder muscles, comprising five muscle groups, during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 28 publications
(45 reference statements)
7
76
1
1
Order By: Relevance
“…Despite the compensatory role previously advocated for LD and TM [Hawkes et al, 2011;Steenbrink et al, 2006], they showed no significant fatigue progression in this study.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Despite the compensatory role previously advocated for LD and TM [Hawkes et al, 2011;Steenbrink et al, 2006], they showed no significant fatigue progression in this study.…”
Section: Discussioncontrasting
confidence: 78%
“…According to the concept of 'adductor muscle co-contraction' during arm elevation [Steenbrink et al, 2006;Steenbrink et al, 2009], contraction of muscles with a line of pull that opposes the superior subluxing force of deltoid can balance the destabilising forces and result in a stable GHJ fulcrum. EMG and computer simulation programmes have identified compensatory roles for LD, TM and PM [Hawkes et al, 2011;Steenbrink et al, 2006;Steenbrink et al, 2009]. Referring to these muscles as 'adductors', can obscure appreciation of their essential role in supporting stability during other shoulder movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally EMG data from deficient SC subjects would be desirable, however, as a first approximation, and since only a 50% SC deficiency was simulated, we assumed that healthy EMG data could be used. This approximation was supported by an EMG study comparing healthy subjects to rotator cuff tear patients and reporting no significant differences in inter-muscular coordination (Hawkes et al, 2012). We associated muscular deficiency with PCSA, as suggested by clinical observations (De Wilde et al, 2012;Goutallier et al, 1994).…”
Section: Discussionsupporting
confidence: 76%
“…The ruptures of the hood are the most common musculotendinous ruptures [4], and the prevalence of massive ruptures ranges from 10% to 40% and increases with age [2,[5][6][7]. The first studies to use the term "solid rupture" date from the decades of 70, 80 [1].…”
Section: Introductionmentioning
confidence: 99%